Vulnerability to natural shocks: Assessing the short-term impact on consumption and poverty of the 2015 flood in Mozambique - Vincenzo Salvucci; Ricardo Santos (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Mozambique is among the most disaster-prone countries in the world. A bigger than usual, and mostly unexpected, flood occurred in the central-northern region of the country in the first few months of 2015, causing huge damage to infrastructures. In this paper, we use a nationally representative household budget survey that was being carried out in the field during those months to assess the short-term impact of the 2015 flood on household consumption and poverty levels. Applying a difference-in-difference approach, we find that, for those exposed to the flood, consumption reduced significantly in the short term, in the range of 11-17 per cent, depending on the specification. Poor households and households living in rural areas were affected significantly more. Poverty levels also increased due to the flood, by about 6 percentage points. These results are relevant for policy planning, natural disaster management, and for ex ante vulnerability assessment in Mozambique and other risk-prone developing countries with similar characteristics.
Keywords: I30; Q51; Q54; Q56; 330; welfare impacts of natural shocks; flood; difference-in-difference; Mozambique